ELSA Speak Application as A Supporting Media for Developing Students’ Speaking Skill - Anugrah Irsan; Nurdin Noni; Sultan Baa (PERFORMANCE: JOURNAL OF ENGLISH EDUCATION AND LITERATURE, 2023)
AbstractThe purpose of this study is to determine the effect of using the Elsa Speak application on improving students' speaking skill. This study used a pre-experimental method with a one-group pre-test post-test approach. The population consisted of ninth grade students at MTs. Al-Hidayah Makassar in the 2022–2023 academic year. A cluster random sampling technique was used, and a sample of 31 students from Class IX was selected. Data were collected through speaking tests conducted before and after the Elsa Speak application treatment. The results showed a significant improvement in students' speaking scores, with the mean score increasing from 52.7 in the pre-test to 74.0 in the post-test. The standard deviation value was 14.0 for the pre-test and 11.6 for the post-test, indicating that the post-test standard deviation was smaller than the pre-test. Furthermore, statistical hypothesis testing using a sample t-test showed that (Sig < α (0.05)), then H0 is rejected and H1 is accepted. These findings suggest that the use of the Elsa Speak application in English language learning can improve students' speaking skill.Keywords: Speaking Skill, Elsa Speak Application.